2012
DOI: 10.1021/la302050m
|View full text |Cite
|
Sign up to set email alerts
|

Zeolite-Templated Carbon Materials for High-Pressure Hydrogen Storage

Abstract: IntroductionAdditional materials characterization and data analysis were performed to supplement the results reported in "Zeolite-Templated Carbon Materials for High Pressure Hydrogen Storage" to assure reproducibility of the results, validate the templated structure of ZTCs, further analyze the micropore character of MSC-30 and ZTCs, and to probe differences in chemical bonding between MSC-30 and ZTCs that could clarify their significant difference in skeletal density.The correlation between BET surface area … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
97
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 116 publications
(110 citation statements)
references
References 34 publications
9
97
0
1
Order By: Relevance
“…4 In summary, it was found that ZTC-3 has chemical properties similar to other ZTCs (being predominantly sp 2 hybridized carbon) and has very high template fidelity, having the structural traits of the best reported examples. 5,6 Its hydrogen adsorption properties are among the highest of reported carbonaceous materials, but are proportional to surface area between 77-298 K as for other carbons.…”
Section: S3 II Materials Propertiesmentioning
confidence: 89%
See 3 more Smart Citations
“…4 In summary, it was found that ZTC-3 has chemical properties similar to other ZTCs (being predominantly sp 2 hybridized carbon) and has very high template fidelity, having the structural traits of the best reported examples. 5,6 Its hydrogen adsorption properties are among the highest of reported carbonaceous materials, but are proportional to surface area between 77-298 K as for other carbons.…”
Section: S3 II Materials Propertiesmentioning
confidence: 89%
“…BET surface areas are reported, as previously discussed. 4 The excess methane capacities measured at 247, 298, and ~523 K from Figure 2 are tabulated for comparison. The skeletal density of ZTC-3, consistent with other ZTCs, is lower than the typical value expected for carbonaceous materials: 1.8 g mL -1 , 81% of the skeletal density of pure graphite.…”
Section: S3 II Materials Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The past decade in particular has witnessed a rapidly growth in diverse applications, especially in the hydrogen storage [11][12][13][14][15][16][17]. In order to meet the requirements of hydrogen storage, a more refined control on the microporosities, surface chemistry and morphology of carbons is very desired [18].…”
Section: Introductionmentioning
confidence: 99%